2017
DOI: 10.1080/21541248.2017.1279725
|View full text |Cite
|
Sign up to set email alerts
|

Rabs on the fly: Functions of Rab GTPases during development

Abstract: The organization of intracellular transport processes is adapted specifically to different cell types, developmental stages, and physiologic requirements. Some protein traffic routes are universal to all cells and constitutively active, while other routes are cell-type specific, transient, and induced under particular conditions only. Small GTPases of the Rab (Ras related in brain) subfamily are conserved across eukaryotes and regulate most intracellular transit pathways. The complete sets of Rab proteins have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
(74 reference statements)
2
7
0
Order By: Relevance
“…Rab7 is a molecule known to regulate late endosomal traffic and is enriched on lysosomes . In addition, Rab7 has often been found on ER exit sites where it co‐localizes with Rab1 . The association of Rab7 with ER/ cis ‐Golgi membranes may indicate the formation of specialized Rab7 compartments that enter non‐canonical trafficking routes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab7 is a molecule known to regulate late endosomal traffic and is enriched on lysosomes . In addition, Rab7 has often been found on ER exit sites where it co‐localizes with Rab1 . The association of Rab7 with ER/ cis ‐Golgi membranes may indicate the formation of specialized Rab7 compartments that enter non‐canonical trafficking routes .…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings regarding the principles of intracellular protein/membrane trafficking have shown that different cell types show a surprising versatility with regards to their usage of the intracellular transport machinery. Although the Rab protein family regulates intracellular trafficking steps across various cell classes (ie, epithelia), the composition, organization and trafficking function of Rab proteins often seems different . Therefore, it is vital to chart and understand intracellular trafficking pathways in as many suitable model systems as possible to describe general transport principles, like continuous or pulsed secretion …”
Section: Discussionmentioning
confidence: 99%
“…Ras-related proteins (Rabs) are a family of GTP-binding proteins (GTPases), and are among the most abundant proteins in exosomes 24 . Rabs are molecules necessary for vesicular movement and plasma membrane docking, and play an important role in the formation, transport, adhesion, anchoring and fusion of vesicles 25 . It is considered to be a molecular switch for vesicular transport between organelles, and participates in mediating exosome secretion 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Rab GTPases along with their effectors, coordinate vesicle trafficking functions such as formation of vesicles, fusion of vesicles, directing vesicles to target membranes (reviewed in (Caviglia et al ., 2019)). In wing discs, many Rab proteins are apically enriched.…”
Section: Resultsmentioning
confidence: 99%